10 Disease penetrance in asymptomatic carriers of familial cardiomyopathy variants. (6th June 2022) - Mahmood, Adil; Morris-Rosendahl, Deborah; Edwards, Matthew; Fleming, Andrew; Homfray, Tessa; Mason, Samantha; Quinn, Ellie; Ware, James; Baksi, John; Prasad, Sanjay; Pantazis, Antonis; Halliday, Brian
Abstract : Introduction: Predictive genetic testing allows the identification of at-risk first-degree relatives of patients with genetic cardiomyopathies. Data on the penetrance of genetic variants associated with cardiomyopathies is limited. The aim of this study was to investigate disease penetrance in asymptomatic carriers of familial cardiomyopathy variants associated with hypertrophic cardiomyopathy (HCM), dilated cardiomyopathy (DCM) and arrhythmogenic right ventricular cardiomyopathy (ARVC). Methods: We included asymptomatic individuals referred to the Royal Brompton Hospital for predictive testing after the finding of a pathogenic or likely pathogenic genetic variant in a first-degree relative with cardiomyopathy between January 2017 and December 2019. Cardiomyopathy diagnosis was defined by international guidelines. Those with a prior diagnosis or signs or symptoms of heart disease at the time of testing were excluded.Results:A total of 105 genotype-positive individuals from 80 families were evaluated (median age 24.9 years [interquartile range: 16.1 to 45.0 years], 51 [48.6%] males). Variants in genes associated with DCM included: TTN n = 16 (51.6%), MYH7 n = 5 (16.1%), LMNA n = 3 (9.7%), TNNI3 n = 3 (9.7%), RBM20 n = 2 (6.5%), BAG3 n = 1 (3.2%), DMD n = 1 (3.2%); variants in genes associated with HCM included: MYBPC3 n = 31 (47.7%), MYH7 n = 25 (38.5%), TPM1 n = 5 (7.7%), PLN n = 1 (1.5%), TNNC1 n = 1 (1.5%), TNNI3 n = 1 (1.5%), TNNT2 n = 1 (1.5%); and variants in genes associated with ARVC included: PKP2 n = 4 (44.4%), DSP n = 4 (44.4%), FLNC n = 1 (11.1%). On first clinical evaluation 2 of 31 carriers of DCM variants were diagnosed with DCM, 5 with hypokinetic non-dilated cardiomyopathy (HNDC) and 4 with isolated left ventricular (LV) dilatation; 10 of 65 carriers of HCM variants were diagnosed with HCM; and 0 of 9 carriers of ARVC variants were diagnosed with ARVC. Over a median follow-up of 2.4 years (interquartile range: 1.0 to 4.3 years) an additional 13 of 84 carriers developed cardiomyopathy phenotypes (0 of 20 DCM, 3 of 20 HNDC, 3 of 20 isolated LV dilatation, 7 of 55 HCM, 0 of 9 ARVC). Furthermore, 2 individuals with DCM/HCM received implantable cardioverter defibrillators and 2 individuals with DCM/HCM received implantable loop recorders. Conclusions: Approximately one-third of asymptomatic carriers of familial cardiomyopathy variants were diagnosed with a cardiomyopathy phenotype at initial screen or during a short follow-up period. This confirms the importance of predictive testing and the need for follow-up of genotype-positive, phenotype-negative individuals. Conflict of Interest: None